An fMRI Study of Concreteness Effects during Spoken Word Recognition in Aging. Preservation or Attenuation? - Roxbury, Tracy; McMahon, Katie; Coulthard, Alan; Copland, David A. (Frontiers in Aging Neuroscience, 2016)
It is unclear whether healthy aging influences concreteness effects (ie. the processing advantage seen for concrete over abstract words) and its associated neural mechanisms. We conducted an fMRI study on young and older healthy adults performing auditory lexical decisions on concrete versus abstract words. We found that spoken comprehension of concrete and abstract words appears relatively preserved for healthy older individuals, including the concreteness effect. This preserved performance was supported by altered activity in left hemisphere regions including the inferior and middle frontal gyri, angular gyrus, and fusiform gyrus. This pattern is consistent with age-related compensatory mechanisms supporting spoken word processing.